Is auditor independence influenced by non-audit services? A stakeholders viewpoint - Muhammad Ramzan; Ishfaq Ahmed; Abdul Rafay (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2020)
The auditor may provide numerous services to their clients covering audit and non-audit services (NAS). These services have been considered asa combination of services offering varying results for client firms. The mixed results reported by past studiesin measuring the relation between NAS and auditor independencehad generated the need of further investigation. Moreover, the dearth of literary evidence from a developing country like Pakistan also created a need for such a study. Considering the gaps left unaddressed in past studies, the current study aims at investigating the possible relationship between NAS and auditor independence. Data of the study was collected from three stakeholders of audit (i.e. accountants, finance managers, and internal auditors). Data collected through the questionnaire proved that various respondent groups have different opinions about the said relationship. It was observed that NAS were believed to have positive, negative and no effects on auditor independence. Moreover, occupational level, experience and educational level of the respondents was also observed to have significant bearing on the opinion aboutNAS and auditor independence relationship. The changing dynamics of the audit profession with abridged trust in itsservices, caused by NAS, have created the need for investigation focusing on views of various stakeholders ofsuch services. This study attempts to provide empirical evidence on the varied perspectives.
Keywords: 330; auditor independence; internal auditors; non-audit services; Pakistan